Characteristics, approaches, and competency learning processes of students in the 21st century - Syarifuddin; Iriani; La Ali Akbar (Balai Diklat Keagamaan Ambon, 2023)
The research aims to describe the competencies of 21st-century students which include the characteristics, approach, and sequence of 4C competencies in the learning process. This information is very important to be used as a reference for schools and teachers in designing curricula and learning instruments. The method used in this study is a literature study. The data source comes from Google Scholar in the period 2018 to 2022. Data were analyzed using a qualitative descriptive approach. The results of the study show that: (1) The competency characteristics of 21st-century students include critical thinking, Communication, Collaboration, and Creativity. (2) The competency learning approach for 21st-century students is to integrate ICT with learning content. (3) The sequence of 4C competencies in the learning process with two versions namely: version 1. starting from Communication-Collaboration – Critical Thinking – Creativity for the MA/SMA/SMK education levels, and version 2. starting from Communication - Collaboration - Creativity - Critical Thinking at the MI/SD and MTs/SMP levels. (4) Critical Thinking competence is still low so it needs attention to be improved for teachers and students.